41.0k views
1 vote
Need full answer if you joke around i will report you please explain

Need full answer if you joke around i will report you please explain-example-1

1 Answer

4 votes
Following PEMDAS, first you multiply:

( (-7)/(3) )x-3=-52\\ (-7x)/(3)-3=-52
Next, you could either multiply all by -3/7 or add 3 to both sides. I will show my work both ways;

Way 1:

(-7x)/(3)-3=-52\\(-7x)/(3)=-49
Now multiply both sides by -3/7:

(-7x)/(3)=-49\\ (-3)/(7)*(-7x)/(3)=-49*(-3)/(7)\\ x=(147)/(7)=21

Way 2:

(-7x)/(3)-3=-52\\ (-3)/(7)*((-7x)/(3)-3)=(-52)*(-3)/(7)\\
Now subtract 9/7 from both sides:

x+(9)/(7)=(156)/(7)\\ x=(147)/(7)=21

Both ways work, just depends on which way's more convenient or easiest :)
Your answer is A, 21.
User Chamath Jeevan
by
5.1k points